Sensorial Characteristics of Coffee (Coffea arabica L. ) varieties in the Alto Paranaíba region - Chalfoun, Sára Maria; Pereira, Marcelo Cláudio; Carvalho, Gladyston Rodrigues; Pereira, Antonio Alves; Savian, Taciana Villela; Santos Botelho, Deila Magna (Coffee Science - ISSN 1984-3909, 2013)
The objective of this study was to verify the sensorial characteristics of grains of 21 Coffea arabica L. cultivars obtained from EPAMIG Experimental Farm in Patrocínio, Minas Gerais, in the Alto Paranaíba Region. The coffee cherries were husked and dried in wooden trays, until 11 to 12% humidity and sent to three Brazilian Specialty Coffee Association BSCA accredited professional coffee tasters. The data were statistically evaluated by multivariate analysis to compare the cultivars and group them. The following cultivars, listed in decreasing order according to the first principal component with scores above 80 points, thus considered to produce superior beverage based on the attributes with the highest scores (flavor,sweetness, balance, acidity, clean beverage and aspect), for the two methods, during the two – year study was cultivar H419-6-2-5-2. The ascendancy of the cultivars and progenies tested, whether derived or not from the Timor Hybrid, did not affect their qualitative performance.